Pengaruh Kopel 20 kV Antar Trafo terhadap Proteksi dan Keandalan Distribusi - Widodo, Yudha Adhe; Sari, Resi Dwi Jayanti Kartika; Arifuddin, Rahman (Elposys: Jurnal Sistem Kelistrikan, 2026)
Lumajang Substation operates three power transformers; however, to date, a 20 kV coupling system between Transformer 2 and Transformer 3 has not yet been implemented. The absence of this coupling potentially leads to transformer overloading, protection coordination mismatch, and reduced reliability of the power supply. This study aims to analyze the impact of implementing a 20 kV inter-transformer coupling on protection system performance and distribution reliability improvement, as indicated by changes in SAIDI, SAIFI, and CAIDI indices at Lumajang Substation. After the implementation of the 20 kV coupling between Transformer 2 and Transformer 3, the SAIDI index decreased from 5.93% to 2.636%, the SAIFI index declined from 137.97% to 72.30%, and the CAIDI index was reduced from 0.269% to 0.242%. Short-circuit current calculations and simulations show that the maximum fault current, represented by a three-phase fault, reaches 17.981 kA, while the minimum fault current, represented by a single-phase-to-ground fault, is 23.092 A. The results yield an OCR setting with an Ipickup of 0.625 A and a TMS of 0.1565 SI, as well as a GFR setting with an Ipickup of 0.1385 A and a TMS of 0.6092 SI. The fault clearing time of the OCR on the coupling is 0.4 seconds, while that of the GFR is 4 seconds. These values fall between the clearing times of the 20 kV incoming feeder and outgoing feeders, thereby satisfying protection coordination principles as verified through simulations using ETAP 19.0.1 software.